Interplay between circulating von Willebrand factor and neutrophils: implications for inflammation, neutrophil function, and von Willebrand factor clearance - Alua Kuanyshbek; Hamideh Yadegari; Jens Müller; Nasim Shahidi Hamedani; Samhitha Urs Ramaraje; Johannes Oldenburg (Haematologica)
Von Willebrand factor (VWF) plays a critical role in hemostasis, and emerging evidence suggests its involvement in inflammation. Our study aimed to investigate the interaction between circulating plasma VWF and neutrophils (polymorphonuclear cells, PMNs), elucidate the fate of VWF after binding, and explore its impact on neutrophil behavior. Neutrophils were isolated from the whole blood of healthy volunteers, and their interaction with plasma VWF was examined ex vivo. Immunofluorescence imaging revealed an enhanced binding of VWF to neutrophils following stimulation with inflammatory agents (PMA, TNFα, and IL-8) and exposure to shear forces, highlighting a previously unknown interaction. Furthermore, immunofluorescence images demonstrated increased co-localization of VWF with the early endosome marker EEA1 and the late endosome marker Rab7 over time, indicating the uptake of VWF by neutrophils subsequent to the binding. This was supported by a significant decrease in VWF antigen levels in the supernatant of cells after stimulation. Moreover, stimulated neutrophils exposed to purified plasma-derived VWF exhibited elevated expression of neutrophil surface markers CD45 and CD66b, indicative of altered neutrophil function related to cell adhesion, migration, and phagocytosis. These findings suggest that VWF binding can modulate neutrophil function, potentially influencing their role in immune responses and inflammation. In summary, our study provides novel insights into the complex interplay between VWF and neutrophils, shedding light on the multifaceted roles of VWF in inflammation. Importantly, we have identified neutrophils as potential cellular mediators involved in the clearance of VWF from circulation, introducing a novel mechanism for VWF removal.